The Effect of Using Self-Assessment Technique towards EFL Students’ Writing Skill - Alkhowarizmi, Annas; Hamdani, Haris (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
This study aims to identify the students’ writing skills before and after using the Self-assessment technique in narrative text and to figure out the positive and significant effect of using the Self-assessment technique in students’ writing achievement narrative text. This research used Quasi-experimental research as a method, to get the data the researcher used a t-test as a research design. To collect the data from the two groups using the test through writing test in the form of simply writing to be used for pre-test and post-test. The researchers used two kinds of classrooms, experimental class, and controlled class. The researchers took 40 students as the sample. the researcher used statistical analysis for analyzing the data. Statistical analysis that the researcher used to study the T-test is SPSS (Statistic Product And Statistic Solution) which examines the significant difference in students’ writing skills between the experimental and control group. The research finding shows that the effect of using the self-assessment technique on students’ writing skills is effective. Based on the t-test result shows that the mean score of the experimental is higher than the control class which obtained 64.50 and the control class obtained a 54.50 score. Furthermore, the result of the data normality test, homogeneity test, and hypothesis test which are claimed that the self-assessment technique has a significant effect on students’ achievement in writing narrative text. Self-assessment was helpful in classroom activity as an experimental class did it. It is also indicated by the higher total scores of students’ writing after the practice of Self-assessment.